Understanding the Radio Variability of Sagittarius A* - Macquart, Jean-pierre; Bower, G. (The American Astronomical Society, 2006)
We determine the characteristics of the 7 mm to 20 cm wavelength radio variability in Sgr A on timescales from days to three decades. The amplitude of the intensity modulation is between 30% and 39% at all wavelengths. Analysis of uniformly sampled data with proper accounting of the sampling errors associated with the light curves shows that Sgr A exhibits no 57 day or 106 day quasi-periodic oscillations, contrary to previous claims. The cause of the variability is investigated by examining a number of plausible scintillation models, enabling those variations that could be attributed to interstellar scintillation to be isolated from those that must be intrinsic to the source. Thinscreen scattering models do not account for the variability amplitude on most timescales. However, models in which the scattering region is extended out to a radius of 50-500 pc from the Galactic center account well for the broad characteristics of the variability on >4 day timescales. The 10% variability on <4 day timescales at 0.7-3 cm appears to be intrinsic to the source. The degree of scintillation variability expected at millimeter wavelengths depends sensitively on the intrinsic source size; the variations, if due to scintillation, would require an intrinsic source size smaller than that expected.